EXPERIMENT ON THE FEEDING OE FRY OF CATFISH HETEROPNEUSTES FOSSILIS - Huq, Molla F; Huque, M K Inamul; Haque, A K M Inamul (Indian Journal of Fisheries, 2011)
An experiment was conducted to determine a suitable feed for the fry of catfish,Heteropneustes fossilis. Of the six types of feed tried, 5 had a common base ofvegetable origin. The feeds diflfered only in their animal protein components. Feed I(with meat oflfal and fish meal) and Feed II (with meat offal and blood meal) and FeedIII (with lysine-cum-methionine) gave the best results. Feed consisting of only fishmeal with no vegetable base resulted in weight reduction of the fry